Isu-Isu Filosofis dalam Pendidikan Menurut George R. Knight - Badani, Abd Quddus al (Lembaga Yasin AlSys, 2021)
Philosophy is the source of science and technology. Talking about philosophy will certainly never end. The book by George R. Knight which has the original title